Efektivitas Pendidikan Karakter Cerdas Format Kelompok untuk Meningkatkan Sikap Nasionalisme Siswa - Darsi Darsi; Zufriani Zufriani; Saaduddin Saaduddin (Journal on Education, 2024)
The issue of nationalism encompasses various challenges and conflicts that arise in the context of nationalism, which is a sense of love and pride for one's country and national identity. Low levels of nationalism are also observed among students. This research aims to examine the effectiveness of the Character Education group format in enhancing nationalism. We employed a quasi-experimental research design, utilizing a pretest-posttest control group design. A total of 30 students affiliated with the Intra-School Student Organization (OSIM) in one of the Madrasah Aliyah schools in Sungai Penuh City participated in the study. The respondents were divided into two groups, namely the experimental and control groups. The scale used in this research was a nationalism scale developed by the researcher. Hypothesis testing was conducted using the Wilcoxon Signed Ranks Test and Kolmogorov-Smirnov 2 Independent Samples Test. The research results indicate that the attitudes of students in both the experimental and control groups toward nationalism were categorized as moderate, both in the pre-test and post-test. However, the study revealed a significant difference between the pre-test and post-test results in the experimental group. Further testing also demonstrated a difference in post-test results between the experimental and control groups. These findings have important implications for the improvement and development of character education curricula in schools. The research also underscores the importance of a holistic approach to character education that encompasses social, emotional, and moral aspects.